Novel Production Method for Plant Polyphenol from Livestock Excrement Using Subcritical Water Reaction. (14th September 2008) - Yamamoto, Mayu; Futamura, Yasuhiro; Fujioka, Kouki; Yamamoto, Kenji
Abstract : Plant polyphenol, including vanillin, is often used as the intermediate materials of the medicines and vanilla flavoring. In agriculture generally vanillin is produced from vanilla plant and in industry from lignin of disposed wood pulp. We have recently developed a method for the production of plant polyphenol with the excrement as a natural resource of lignin, of the herbivorous animals, by using the subcritical water. The method for using the subcritical water is superior to that of the supercritical water because in the latter complete decomposition occurs. We have successfully produced the vanillin, protocatechuic acid, vanillic acid, and syringic acid in products. Our method is simpler and more efficient not only because it requires the shorter treatment time but also because it releases less amount of carbon dioxide into the atmosphere.